2014
DOI: 10.1007/s00109-014-1220-8
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol prevents pathological but not physiological cardiac hypertrophy

Abstract: Resveratrol differentially regulates pathological and physiological cardiac hypertrophy. Resveratrol dose selectively inhibits pathological cardiac signaling pathways. Resveratrol inhibits NFAT-dependent transcription. At low concentrations, effects of resveratrol are AMPK-independent. Resveratrol may be used to selectively treat pathological cardiac hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…Consistent with previous studies,7, 25 Rev substantially decreased the size of cardiomyocytes. Results from the current study showed that the dosage (10 μmol/L of Rev) markedly reduced the size of cardiomyocytes in vitro (Figure 1).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous studies,7, 25 Rev substantially decreased the size of cardiomyocytes. Results from the current study showed that the dosage (10 μmol/L of Rev) markedly reduced the size of cardiomyocytes in vitro (Figure 1).…”
Section: Resultssupporting
confidence: 92%
“…The data from a recent famous study showed that Rev had a markedly inhibitory role on NFAT‐dependent transcription in cardiomyocytes, which suggested that Rev could prevent pathological cardiac hypertrophy by blocking NFAT‐mediated regulation of gene transcription 7. Furthermore, they also showed that Rev could activate AMPK and inhibit Akt signaling in the cardiac myocyte, and these Rev‐mediated effects could inhibit cardiac myocyte hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Fasudil is the only ROCK inhibitor approved for human use at present, although its specific effect has not been evaluated at a cardiac level [53]. Resveratrol and pioglitazone have relevant antioxidant cardiac properties and have also been suggested to inhibit cardiac hypertrophy [54,55].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Resveratrol is one kind of the antioxidant compound and widely exists in peanuts, berries, grapes and some China herbs [16][17][18]. Recently, more and more studies uncover that Resveratrol has anticancer actions on a variety of cancers [19].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Resveratrol can protect hearts against cardiovascular diseases. For example, Resveratrol was shown to suppress left ventricular hypertrophy and heart failure [17,22]. Resveratrol treatment also inhibits ischemia/reperfusion injury and ventricular arrhythmias [23].…”
Section: Introductionmentioning
confidence: 99%